MOTIVATION OF SOCIALLY RESPONSIBLE BUSINESS ACTIVITIES (ANALYSIS OF RESEARCH BY WESTERN SCIENTISTS) - KOMPANIETS, Viktoriia; BELA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This publication examines the determinants and motives of socially responsible business activities based on the works of Western experts. Socially responsible business activity is determined by the influence of determinants of the external environment, which can be classified as economic, legal, social, or instrumental and institutional. They are strategic in terms of business goals and results. A different angle of detail of external determinants allows us to identify such important components as the state of the social environment; the presence and characteristics of ethical leadership; integration of social responsibility values into the culture of the organization; a competitive business environment combined with conscious consumers that creates value for companies ’ reputation. Studying the external and internal motivation of socially responsible business activities, Western researchers have found that large companies are more motivated by external incentives, while small and medium-sized businesses rely on internal motives. Among them, the most significant are the values and beliefs of managers (owners), their conscience, and their understanding of their duty to society. In our opinion, internal motivation is based on such determinants as a system of values formed in an ethical direction; a developed conscience; and the desire for personal development. Internal and external motivations of socially responsible business activities are correlated, which logically follows from the social conditionality of human behavior. The moral climate in society and the institutional conditions that support socially responsible business behavior are more important external determinants that strengthen the internal motivation of management for appropriate behavior. To find effective economic incentives to promote socially responsible business activities, both organizations and the governments of countries must use knowledge about the specifics of its motivation among management and entrepreneurs. The perspective of our research is systematic, conceptually based empirical studies of the peculiarities of motivation of socially responsible activity of Ukrainian business in which the first step is to study the experience of Western scientists.